How the CIOMS guidelines contribute to fair inclusion of pregnant women in research. (20th October 2018) - van der Graaf, Rieke; van der Zande, Indira S. E.; van Delden, Johannes J. M.
Abstract: As early as 2002, CIOMS stated that pregnant women should be presumed eligible for participation in research. Despite this position and calls of other well‐recognized organizations, the health needs of pregnant women in research remain grossly under‐researched. Although the presumption of eligibility remains unchanged, the revision of the 2002 CIOMS International ethical guidelines for biomedical research involving human subjects involved a substantive rewrite of the guidance on research with pregnant women and related guidelines, such as those on fair inclusion and vulnerability. However, close reading of the guidelines reveals morally relevant different approaches to fair inclusion of pregnant women and other under‐represented groups, such as children and incompetents. Where CIOMS sets out that children and adolescents must be included unless a good scientific reason justifies their exclusion, no such claim of having to justify exclusion appears in the guideline on pregnant women. Instead, CIOMS claims that research relevant to pregnant women's health needs must be promoted. This paper analyses how and to what extent the guideline on pregnant women differs from other guidance on fair inclusion in the document. Accordingly, the paper evaluates to what extent the current phrasing may contribute to fair inclusion of pregnant women in research. We will conclude that a system change towards a learning health system is essential to break down the status quo of knowledge generation in the field of medication use during pregnancy and argue that the CIOMS guidelines allow for this system change.